Proses Pemurnian Selulosa Pelepah Sawit Sebagai Bahan Baku Nitrolesulosa Dengan Variasi pH Dan Konsentrasi H2O2 - Rianto Harpendi; Padil Padil; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
One of the raw materials for propellant or explosive double base type is nitrocellulose. Availability of cellulose which is the main component of biomass is very abundant in Indonesia, particularly solid waste palm oil industry. With cellulose content of 34.89%, palm midrib is one solid waste palm with potential to be used as the main raw material cellulose. Purity cellulose levels that must be achieved to produce nitrocellulose propellant as raw material is more than 92%. So as to improve the purity of the cellulose in the palm midrib must be purified using hydrogen peroxide, which is initiated by the hydrolysis with EFB ash extract. Hydrogen peroxide is a chemical that can be used for the bleaching process, because this compound is more environmentally friendly than chlorine. The purpose of this is to obtain the best conditions to obtain cellulose purity of more than 92%. The bleaching process is done by varying the concentration of hydrogen peroxide (1%, 2%, 3%, 4%, 5%) and pH (8, 9, 10, 11, 12). Pulp composition analysis of purified cellulose. Obtained the best process conditions is the concentration of 3% hydrogen peroxide and pH 9 with 95.11% purity cellulose. Keywords : Palm Midrib, Bleaching, Hydrogen Peroxide, Cellulose